Love, Brooklyn [videorecording (DVD)] - Zimmerman, Paul (Screenwriter); Beharie, Nicole; Holland, André; Wise, DeWanda; Boone, Joshua; Haven, Jack; Patterson, Carra; Reese, Cadence; Sengbloh, Saycon, 1977-; Freeman, Cassandra, 1978-; Wood, Roy, Jr., 1978-; Mickens, Missy; et al. (Kino Lorber, 2025)
"A writer navigates complicated relationships with his ex, an art gallery owner, and his current lover, a recently widowed mother, with the support of his best friend. A modern romance set against the rapidly changing landscape of Brooklyn, New York."--